Practices regarding modern contraceptive use among female students. A comparative study between the university of Zimbabwe and Chinhoyi university of technology, Zimbabwe - Toweka Andrea; Moyo Stanzia; Mhloyi Marvellous; Makochekanwa Albert; Mandizadza Enock (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2021)
Modern contraceptive use prevents the risk of unplanned pregnancies, unsafe abortions and STIs. Yet little is known about the use of modern contraceptives by female students in tertiary institutions given that available studies have been using women in the reproductive age as the unit of analysis. The study was conducted at the University of Zimbabwe and the Chinhoyi University of Technology. The study triangulated quantitative and qualitative research methods. A survey with 770 female students, 537 from the University of Zimbabwe and 233 from the Chinhoyi University of Technology, to assess the magnitude of modern contraceptive use among female students and explore the facilitating and inhibiting factors underlying contraceptive use. Qualitative data were collected from eight face-to-face in-depth interviews, eight face-to-face focus group discussions and four face-to-face key informant interviews. Modern contraceptive use was high, 98%, however an insignificant variation was noted, 98% at UZ and 97% at CUT. Male condoms were commonly used by students throughout their sexual activities with marginal variations noted- 98% at UZ and 97% at CUT. Female students accessed contraceptives from the SAYWHAT resource centre although the prevalence was high among students at CUT, 95%, when compared to UZ students, 87%. Therefore the study recommends that the preferred modern contraceptives should be available and accessible to students. Information of safe sex practices should be disseminated to students to ensure consistency in contraceptive use. Contraceptive distribution points should be accessible to students to increase contraceptive uptake.